Más allá de un cuarto propio: trece novelas en pugna en el siglo XXI. - ARAÚJO, NARA (Revista de Estudios Hispánicos)
The article focuses on a group of 13 novels written by women between 2003 and 2007 including "Video, Graffiti y otros tatuajes" by Ana Luz García Calzada, "Las edades transparentes" by Lourdes González and "Otras plegarias atendidas" by Mylene Fernández Pintado. The author discusses the contribution of each novel to the body of Cuban literature and comments on several commonalities including experimental writing and themes related to women's gender consciousness, identity and emancipation.